Understanding the Impact of Financial Literacy on Economic Awareness Among Senior Secondary Students in Delhi: A Qualitative Exploration - Lovekesh, Lovekesh; Ahirwar, Sanjay; Kumar, Binod; Malik, Ruby; Sharma, Preeti; Kumar, Parveen; Acharya, Raghav (Journal of Neonatal Surgery, 2025)
This qualitative study explored how financial literacy influenced economic awareness among senior secondary students in Delhi. Through in-depth interviews and focus group discussions, the study examined students' understanding of financial concepts such as saving, budgeting, banking, and digital transactions. The findings revealed that while students had basic financial knowledge, they lacked deeper insights into practical financial decision-making and economic participation. The study also identified key challenges, including the absence of financial education in school curricula, limited real-life financial exposure, and insufficient teacher training. Students expressed a strong need for structured financial education that included practical learning experiences, guest lectures, and digital financial literacy training. The study concluded that integrating financial literacy into school programs could significantly enhance students' confidence and preparedness for financial responsibilities in adulthood. The research emphasized the importance of financial education in shaping economically aware and responsible future citizens.